Sabotage - Kenyon, Sherrilyn, 1965- (Chronicles of Nick: Shadows of fire, 2023)
"The world of the Dark-Hunters is unlike anything you've ever seen before. It's dark. It's gritty. It's dangerous... And it's a whole lot of unexpected action and snarky comebacks. My name is Nick Gautier and I was born to end the world. Or so I thought. For years, I believed my destiny was beyond my control. But the Fates love to play with folks and I seem to be their favorite punchline. Just when My crew and I thought we were done with the Apocalypse, the Fates had dragged back for another round. Now, we have to stop the Powers-That-Be and my future son or the ones I love and cherish will become memories. It's a demon-eat-demon world and we are all the stands between humanity and total subjugation"--Back cover.